Single-shot late Gd enhancement imaging of myocardial infarction with retrospectively adjustable contrast and heart-phase - Wech, Tobias; Tran-Gia, Johannes; Rützel, Felix; Klink, Thorsten; Bley, Thorsten A.; Köstler, Herbert (Magnetic Resonance Imaging, 2018)
Object To enable a retrospective adjustment of image contrast and heart phase in inversion recovery prepared late gadolinium enhancement (LE) imaging in the myocardium. Materials and methods After one inversion pulse, unsegmented data were acquired over multiple cardiac cycles using a radial spoiled gradient-echo sequence with golden angle increments between subsequent readouts. Model-based acceleration of parameter mapping (MAP) was combined with an image registration technique (“MOCO-MAP”) to enable the reconstruction of images with arbitrary inversion time TI. Results MOCO-MAP allowed the reconstruction of LE images with arbitrary TI for arbitrary cardiac phases in four patients suffering from myocardial infarction. Regions with LE agreed well between the MOCO-MAP and the segmented techniques typically applied in clinical routine. Conclusions MOCO-MAP delivers LE images with arbitrary and thus retrospectively optimized contrast between vital and diseased tissue, without the need for time-consuming TI scouting.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Cardiomyopathies; Compressed sensing; Delayed myocardial enhancement MRI; Heart; Late Enhancement imaging; Magnetic resonance imaging; Model-based reconstruction; Myocardial infarction; Myocardium